Somatotopic fascicular organization of the human sciatic nerve demonstrated by MR neurography - Bäumer, Philipp; Weiler, Markus; Bendszus, Martin; Pham, Mirko (Neurology, 2015)
Objectives: To investigate whether the human sciatic nerve might have a consistent somatotopic organization according to proximal fascicle input by spinal nerves. Methods: Twelve patients (55.3 ± 15.5 years) with confirmed lesions of either the L5 or S1 spinal nerve root underwent magnetic resonance neurography of sciatic nerve fascicles including thigh and knee levels (T2-weighted sequence with fat saturation, repetition time/echo time 7,552/52 milliseconds, voxel size 0.27 × 0.27 × 3.0 mm3). Twenty healthy subjects and 12 additional patients with an established diagnosis of peripheral polyneuropathy served as 2 separate age- and sex-matched control groups. Two blinded readers assessed patients and controls for presence of distinct lesion patterns. Spatial maps of normalized T2 signal were rendered after segmentation and coregistration of sciatic nerve voxels to detect fascicle lesion patterns. Results: A clear somatotopic distribution of nerve fascicles was observed on cross-sections along the entire course of the sciatic nerve and was distinct between patients with L5 and those with S1 lesions. Fascicles emerging from L5 were ordered in anterolateral positions within sciatic nerve cross-sections, while fascicles emerging from S1 appeared posteromedially. Visual assessment discriminated these somatotopic lesions in all cases from both healthy and polyneuropathy controls. Conclusion: A distinct pattern of somatotopy was identified within the sciatic nerve according to proximal fascicle input by L5 and S1 spinal nerves. Knowledge of human nerve somatotopy may have clinically useful implications in imaging-aided diagnosis of neuropathies.